Blood Center Testing Allows the Detection and Rapid Treatment of Acute and Recent HIV Infection - Karin van den Berg; Marion Vermeulen; Sonia Bakkour; Mars Stone; Genevieve Jacobs; Cynthia Nyoni; Coreen Barker; Christopher McClure; Darryl Creel; Eduard Grebe; Nareg Roubinian; Ute Jentsch; et al. (Viruses, 2022)
Blood donations in South Africa are tested for HIV RNA using individual donation NAT (ID-NAT), allowing detection and rapid antiretroviral therapy (ART) of acute HIV infections. We enrolled a cohort of acute and recent HIV-infected blood donation candidates in South Africa in 2015–2018, measured HIV antibody, ID-NAT, and recency of infection <195 days (Sedia LAg) at enrollment and initiated early ART. A small cohort of HIV elite controllers was followed without treatment. HIV reservoir measurements included ultrasensitive plasma RNA, cell-associated HIV RNA, and total DNA. Enrollment of 18 Fiebig I–III and 45 Fiebig IV–VI HIV clade C subjects occurred a median of 18 days after index blood donation. ART was administered successfully and compliance with follow-up visits was excellent. There were only minimal differences in HIV reservoir between ART initiation in Fiebig stages I–III vs. IV–VI, but ART noncompliance increased HIV reservoir. In 11 untreated HIV elite controllers, HIV reservoir levels were similar to or higher than those seen in our early treated cohort. National blood services can identify acute HIV cohorts for subsequent HIV cure research studies. Among HIV clade C-infected donors, HIV reservoir differed little by Fiebig stage at treatment initiation, but was smaller than in chronically treated HIV and those with ART noncompliance.